A retrospective observational study of glucocorticoid-induced diabetes mellitus with IgA nephropathy treated with tonsillectomy plus methylprednisolone pulse therapy - Miyawaki, Yoshia (PLoS One, 2017)
AIMS: To evaluate the incidence of GC-DM among patients with immunoglobulin A nephropathy (IgAN) and to confirm the risk factors for the development of GC-DM. METHODS: The medical records of patients with IgAN newly treated with the protocol of tonsillectomy combined with steroid pulse therapy were reviewed. The primary outcome was the development of GC-DM within the hospitalization period and during one year of follow-up. RESULTS: During hospitalization, 19 of the 95 patients developed GC-DM (20.0%), and the patients with GC-DM were significantly older and had a higher rate of family history of diabetes and higher HbA1c levels. The prevalence of hypertension was higher and the eGFR was numerically lower in patients with GC-DM than in those without. Older age (≥45 years) and a family history of diabetes emerged as independent risk factors for the development of GC-DM (odds ratio [OR], 6.3 and 95% confidence interval [CI], 1.6–27.6; OR, 4.4 and 95% CI, 1.2–16.6, respectively). No patients were newly diagnosed with GC-DM during 1-year observation period at out-patient clinic. CONCLUSIONS: Among the patients with IgAN, 20% developed GC-DM during the hospitalization period, confirming the family history of diabetes is clinically necessary before starting GC therapy.